A neo-darwinian foundation of evolutionary economics: With an application to the theory of the firm - Fritz Rahmeyer (Universität Augsburg, Institut für Volkswirtschaftslehre, 2010)
The focus of evolutionary economics is a process of continuous economic and organizational change. Currently there is no agreement on the explanation of economic evolution. Rather there are competing interpretations. To achieve a common understanding of economic evolution, from the perspective of the history of economic thought, at first the theoretical approaches of Schumpeter and Marshall with regard to economic development or evolution are dealt with. After that, a concept of socio-economic evolution in broad agreement with evolution in nature is elaborated. It is summed up in the version of a generalized Darwinism. In this, evolution is seen as a process of change that leads to the adaptation of complex systems, the result of the causal interaction among variation, selection and retention of variety. As a (slightly) different interpretation the presently predominating approach of neo-Schumpeterian evolutionary economics is presented. It has gained wide application to the theory of innovation and later - based on Penrose - to resource-based theories of the firm. In this the dynamic process of the creation and exploitation of resources, mainly knowledge, turns out to be the centre of attention of an evolutionary theory of the firm.
urn:nbn:de:bvb:384-opus4-711186
Keywords: A12; B15; B52; D21; 330; Economic evolution; Schumpeter and Marshall; Generalized Darwinism; Evolutionary theory of the firm; Evolutionsökonomik; Bioökonomik; Theorie der Unternehmung; Dogmengeschichte; Theorie